Platelet and immune signature associated with a rapid response to the BNT162b2 mRNA COVID‐19 vaccine. (26th January 2022) - Flego, Davide; Cesaroni, Simone; Romiti, Giulio F.; Corica, Bernadette; Marrapodi, Ramona; Scafa, Noemi; Maiorca, Francesca; Lombardi, Ludovica; Pallucci, Davide; Pulcinelli, Fabio; Raparelli, Valeria; Visentini, Marcella; et al.
Abstract: Background: A rapid immune response is critical to ensure effective protection against COVID‐19. Platelets are first‐line sentinels of the vascular system able to rapidly alert and stimulate the immune system. However, their role in the immune response to vaccines is not known. Objective: To identify features of the platelet‐immune crosstalk that would provide an early readout of vaccine efficacy in adults who received the mRNA‐based COVID‐19 vaccine (BNT162b2). Methods: We prospectively enrolled 11 young healthy volunteers (54% females, median age: 28 years) who received two doses of BNT162b2, 21 days apart, and we studied their platelet and immune response before and after each dose of the vaccine (3 and 10 ± 2 days post‐injection), in relation to the kinetics of the humoral response. Results: Participants achieving an effective level of neutralizing antibodies before the second dose of the vaccine (fast responders) had a higher leukocyte count, mounted a rapid cytokine response that incremented further after the second dose, and an elevated platelet turnover that ensured platelet count stability. Their circulating platelets were not more reactive but expressed lower surface levels of the immunoreceptor tyrosine‐based inhibitory motif (ITIM)‐coupled receptor CD31 (PECAM‐1) compared to slow responders, and formed specific platelet‐leukocyte aggregates, with B cells, just 3 days after the first dose, and with non‐classical monocytes and eosinophils. Conclusion: We identified features of the platelet‐immune crosstalk that are associated with the development of a rapid humoral response to an mRNA‐based vaccine (BNT162b2) and that could be exploited as early biomarkers of vaccine efficacy.